Identification of Boronic Acid Derivatives as an Active Form of N-Alkylaminoferrocene-Based Anticancer Prodrugs and Their Radiolabeling with 18F - Daum, Steffen; Toms, Johannes; Reshetnikov, Viktor; Özkan, Hülya; Hampel, Frank; Maschauer, Simone; Hakimioun, Amir Hossein; Beierlein, Frank; Sellner, Leopold; Schmitt, Michael; Prante, Olaf; Mokhir, Andriy (Bioconjugate Chemistry, 2019)
N-Alkylaminoferrocene (NAAF)-based prodrugs are activated in the presence of elevated amounts of reactive oxygen species (ROS), which corresponds to cancer specific conditions, with formation of NAAF and p-quinone methide. Both products act synergistically by increasing oxidative stress in cancer cells that causes their death. Though it has already been demonstrated that the best prodrugs of this type retain their antitumor activity in vivo, the effects were found to be substantially weaker than those observed in cell cultures. Moreover, the mechanistic studies of these compounds in vivo are missing. For clarification of these important questions, labeling of the prodrugs with radioactive moieties would be necessary. In this paper, we first observed that the representative NAAF-based prodrugs are hydrolyzed in dilute aqueous solutions to the corresponding arylboronic acids. We confirmed that these products are responsible for ROS amplification and anticancer properties of the parent prodrugs. Next, we developed the efficient synthetic protocol for radiolabeling the hydrolyzed NAAF-based prodrugs by [18F]fluoroglucosylation under the conditions of the copper(I)-catalyzed azide–alkyne 1,3-dipolar cycloaddition and used this protocol to prepare one representative hydrolyzed NAAF-based prodrug radiolabeled with 18F. Finally, we studied the stability of the 18F-labeled compound in human serum in vitro and in rat blood in vivo and obtained preliminary data on its biodistribution in vivo in mice carrying pancreatic (AR42J) and prostate (PC3) tumors by applying PET imaging studies. The compound described in this paper will help to understand in vivo effects (e.g., pharmacokinetics, accumulation in organs, the nature of side effects) of these prodrugs that will strongly contribute to their advancement to clinical trial